2021
DOI: 10.3892/wasj.2021.94
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide as an early treatment to reduce the intensity of COVID‑19 outbreaks among health personnel

Abstract: The use of nitazoxanide has previously yielded successful results in vitro against the coronavirus. The aim of the present study was to examine the efficacy of the use of nitazoxanide at an early stage among healthcare workers exhibiting symptoms of COVID-19. This was a prospective study carried out in 2020. Healthcare personnel who presented with COVID-19 symptoms, in different 3 hospitals were invited to take Paramix (nitazoxanide), 500 mg orally, every 6 h for 2 days and then 500 mg twice a day for 4 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Similarly, a small randomized, placebo-controlled trial involving mild COVID-19 patients showed that early nitazoxanide significantly eliminated; 29.9% of patients in the nitazoxanide arm versus 18.2% in the placebo arm (p=0.009) and reduced viral load (p=0.006) as compared to placebo with no serious adverse events and at the 1-week follow-up, 78% in the nitazoxanide arm versus 57% in the placebo arm reported complete resolution of symptoms (p=0.048) [33] and later it was published [34]. Recently, a prospective study has also suggested that early use of nitazoxanide might decrease COVID-19 complications among healthcare personnel [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a small randomized, placebo-controlled trial involving mild COVID-19 patients showed that early nitazoxanide significantly eliminated; 29.9% of patients in the nitazoxanide arm versus 18.2% in the placebo arm (p=0.009) and reduced viral load (p=0.006) as compared to placebo with no serious adverse events and at the 1-week follow-up, 78% in the nitazoxanide arm versus 57% in the placebo arm reported complete resolution of symptoms (p=0.048) [33] and later it was published [34]. Recently, a prospective study has also suggested that early use of nitazoxanide might decrease COVID-19 complications among healthcare personnel [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore,78% of patients in the nitazoxanide arm versus 57% in the placebo arm showed complete resolution of symptoms after 1-week follow-up (p = 0.048) [33,34]. Moreover, A prospective study has recently suggested that early use of nitazoxanide might decrease COVID-19 complications among healthcare personnel [35].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we would like to mention that we have previously, on April 2020, suggested a pioneering combination of the FDA approved inexpensive drugs; nitazoxanide/azithromycin to be used for early COVID-19 management basing on a hypothesis attributing their potential benefit to the ability to augment and restore our natural interferon homeostasis [18]. Later, some clinical studies started to prove the validity of our recommendation for this combination [19][20][21]. Interestingly, nitazoxanide was shown to inhibit the production of several pro-inflammatory cytokines including IL-6, IL-8 and TNF-α in peripheral blood mononuclear cells [22] and it was also shown, in an in vivo murine model and macrophage cell line, to decrease IL-6 production induced by thioglycollate and lipopolysaccharide, respectively to be suggested as a promising lead drug for diseases associated with overproduction of IL-6 [12] and for its anti-IL-6 properties and other potential effects, nitazoxanide was suggested to be tested, either acting alone or as coadjuvant, in the treatment of ovarian carcinoma [23].…”
Section: Nitazoxanide/azithromycin Combination For Covid-19mentioning
confidence: 96%